Dom Camilo v. Peppone : Josué Guimarães, pseudônimos e vozes em conflito - Palagen, Elisângela de Britto (2016)
The main purpose of this research is to interpret journalistic chronicles of the columns Our little world and one day after the other, published in 1954 by "chroniclers" fictitious Peppone and D. Camillo, both pseudonyms used by the southern writer Josué Guimarães, listed as constructed from the speeches that preceded them, as well as the historical relations that were inserted, presenting them as important discursive events that reflected the social context of the time they were published, making them true literary works. It was defined as corpora for this research the chronic representing the struggle between the socialist and capitalist ideologies represented by film characters that Josué Guimarães seized to provide its pseudonyms. Also chronic presenting evidence were analyzed interdiscursive with the work The Walls of Jericho, written by Josué Guimarães, as this is established as the speech enhancer past chronic. As for being established as statements that interact with each other in an antagonistic-ideological form, this search interprets, from the theoretical assumptions of Mikhail Bakhtin (1997, 1998, 2003, 2006) related to dialogism and polyphony, the inserted in chronic voices debating on two divergent social and political forces: the socialism and capitalism. It is proposed that Similarly, a study of genres from Bakhtinian precepts, emphasizing the chronic discursive genre. For the analysis of chronic became necessary contextualization historical in which was inserted the writer, journalist and politician Josué Guimarães to, consequently, appreciate the composition of groups of speakers who signed columns Around the world and One day after the other as socio-historically constituted subject. Per through the concept that a subject is defined as the only being-event, socio-historically situated and culturally imbued with ideologies, constituted in relation to other subjects, settles this research that aims to rebuild the memory of journalist and writer Josué Guimarães, imposing figure in the press and in Rio Grande do Sul and national literature through the legacy left his family to Literary Collection Josué Guimarães (ALJOG / UPF). the parameters proposed for the analysis of this research have highlighted that subject, history and ideologies are inseparable, and that in the creation of awareness of this subject, the voices preterit are responsible for the statements and the responsive acts that these are recurrent